Managing tropical forages field genebanks at CIAT - Maass, Brigitte L.; Ortíz Escobar, Amanda (International Center for Tropical Agriculture, 1996)
Two main reasons are identified for maintaining permanent field collections of tropical forages: (1) the inability to produce reliably sufficient and viable seed, and (2) outcrossing or highly heterozygous species where particular genotypes or populations should be conserved. The history, origin and management of tropical forage field collections maintained at CIAT are described. Details are given for each of the collections, i.e., the grasses -Andropogon, Bracharia and Panicum, and the legumes-Arachis and Leucaena. Management experiences are given, and research needs for proper management are defined